Challenges in the Integration of Digital Literacy in English Language Teaching - Cornelia, Uspessy Shuha; Sulistyaningrum , Siti Drivoka (UICELL, 2023)
With the tremendous technological developments of this century blurring the line between online and offline activities, the emergence of the digital world is inevitable. By the proliferation of new technologies, digital awareness for the safe, appropriate and efficient selection and management of digital resources for digital learning education is becoming important. In the context of English Language Teaching, the proportion of ICT in the learning process is increasingly high. However, there may be some barriers that affect the familiarity and motivation of the relevant learning components. To answer the research question on challenging aspect of the integration of digital literacy in ELT, a systematic review of 20 articles sourced from Google scholar is executed. It reveals that the challenges are generally resulted from students, teachers, and schools’ preparedness; which involves low operational skill; limited access to computer and internet; and the lack of proper learning materials that covers media literacy. Keywords: Digital Literacy, English Language Teaching, Systematic Literature Review